Kendala dan Strategi RTQ Pondok Qori dalam Meningkatkan Hafalan Santri - Takwin Takwin; Suswati Hendriani (Departement of Mathematics Education, 2023)
This study aims to see and find out what obstacles and strategies are made and implemented by the foundation, ustad and ustazah to increase the memorization of the Qur'an for all students at RTQ Pondok Qori, useful for RTQ or other tafiz houses to implement strategies that Prepared and carried out by RTQ Pondok Qori in order to facilitate the process of memorizing the Qur'an for students who carry it out. This research uses a qualitative descriptive approach, which will describe the strategies used by RTQ Pondok Qori in the learning process of memorizing the Qur'an by the students. students for the ongoing memorization process at the tafiz house, the weather affects the concentration of students in the process of memorizing the Qur'an in the classroom, and the lack of support from parents to repeat memorization at home. There are 5 strategies carried out by RTQ Pondok Qori in increasing the memorization of students including, multiple repetition strategy, Using the wahda method, Using one type of manuscript, Understanding verse by verse memorized, and Paying attention to similar verses